From chicken to salad: Cooking salt as a potential vehicle of Salmonella spp. and Listeria monocytogenes cross-contamination. (July 2022) - Alves, Ângela; Santos-Ferreira, Nânci; Magalhães, Rui; Ferreira, Vânia; Teixeira, Paula
Abstract: Epidemiological studies show that improper food handling practices at home account for a significant portion of foodborne illness cases. Mishandling of raw meat during meal preparation is one of the most frequent hazardous behaviours reported in observational research studies that potentially contributes to illness occurrence, particularly through the transfer of microbial pathogens from the raw meat to ready-to-eat (RTE) foods. This study evaluated the transfer of two major foodborne pathogens, Salmonella enterica and Listeria monocytogenes, from artificially contaminated chicken meat to lettuce via cooking salt (used for seasoning) during simulated domestic handling practices. Pieces of chicken breast fillets were spiked with five different loads (from ca. 1 to 5 Log CFU/g) of a multi-strain cocktail of either S. enterica or L. monocytogenes. Hands of volunteers (gloved) contaminated by handling the chicken, stirred the cooking salt that was further used to season lettuce leaves. A total of 15 events of cross-contamination (three volunteers and five bacterial loads) were tested for each pathogen. Immediately after the events, S. enterica was isolated from all the cooking salt samples (n = 15) and from 12 samples of seasoned lettuce; whereas L. monocytogenes was isolated from 13 salt samples and from all the seasoned lettuce samples (n = 15) . In addition, S. enterica and L. monocytogenes were able to survive in artificially contaminated salt (with a water activity of 0.49) for, at least, 146 days and 126 days, respectively. The ability of these foodborne pathogens to survive for a long time in cooking salt, make it a good vehicle for transmission and cross-contamination if consumers do not adopt good hygiene practices when preparing meals. Highlights: Pathogens may contaminate cooking salt via cross-contamination from unwashed hands. Salmonella enterica and Listeria monocytogenes survive on salt for several weeks. Pathogens are transmitted from contaminated chicken to hands, and then to salt. L. monocytogenes and S. enterica present in lettuce seasoned with contaminated salt.